2020
DOI: 10.3390/app10051683
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Thermal Stability of Magnesium Oxychloride 5Mg(OH)2∙MgCl2∙8H2O

Abstract: Today, low-energy and low-carbon footprint alternatives to Portland cement are searched because of huge CO2 emissions coming from Portland clinker calcination. Because of some superior properties of magnesium oxychloride cement (MOC) and the lower carbon footprint of its production, MOC became an intensively studied material with high application potential for the design and development of construction products. In this contribution, magnesium oxychloride with stoichiometry 5Mg(OH)2∙MgCl2∙8H2O (Phase 5) was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 30 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…This process MOC phases and MOC-based composites have been intensively studied in recent years. Synthesis, structure, and the thermal stability of magnesium oxychlorides in particular were studied in detail [6,7]. MOC is a non-hydraulic versatile binder with specific properties, which make it superior to PC.…”
Section: Introductionmentioning
confidence: 99%
“…This process MOC phases and MOC-based composites have been intensively studied in recent years. Synthesis, structure, and the thermal stability of magnesium oxychlorides in particular were studied in detail [6,7]. MOC is a non-hydraulic versatile binder with specific properties, which make it superior to PC.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that a 5•1•8 phase was present in crosslinked needle-and rod-shaped crystals in the MOC, which endowed it with good mechanical properties [23,24]. When the molar ratio of MgO/MgCl 2 was less than 6, the MgO content in the hydration products increased with an increase in the MgO/MgCl 2 molar ratio, which made the original solution more alkaline and ensured the stability of the MOC phase [7].…”
Section: Derivation Of Formula (Df)mentioning
confidence: 93%
“…The strength of MOC can be reduced with the introduction of waste [14]. The MgCl 2 used in the laboratory or small amounts of MgCl 2 used to study MOC material are obtained as high-purity raw materials [23,24], and some errors may be involved in practical industrial applications when an impure raw material is used [25]. Due to the number of raw materials, their relationships with concrete performance have a great impact [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies describing the development of phase 3 and phase 5 in the reaction process show the progress of their formation. The stoichiometric phase 3 is fully formed (>99 wt.% of the sample) after only 36 h. The study of formation of the phase 5 described the formation process similarly, determining the formation time of the pure phase 5 (>99 wt.% of the sample) to 96 h [ 28 , 29 ]. Concerning the strength development, preceding research has shown the significant increase in the compressive strength in the first seven days of curing.…”
Section: Introductionmentioning
confidence: 99%